Retained Shrapnel from a Blast Injury as a Rare Cause of Secondary Osteoarthritis of the Hip Joint: A Case Report and Review of Literature - Oshan Basnayake; Ahamed Nihaj; Ranji Pitagampalage; Umesh Jayarajah; Yasith Mathangasinghe; Harsha Mendis (Case Reports in Surgery)
Background. Complications related to intra-articular retained shrapnel are rare and primarily depend on the anatomical location and the reaction with the surrounding tissue. Retained bodies causing severe osteoarthritis with bone destruction and limb shortening are extremely rare. We describe a rare occurrence of retained shrapnel, possibly iron nails causing a late presentation of grade 4 secondary osteoarthritis of the hip joint with destruction of the femoral head and limb shortening. Case Presentation. A 74-year-old otherwise healthy Sri Lankan male with a history of blast injury to the right hip 35 years ago presented with an isolated, right sided mild hip pain with a progressive limp for an 8-year duration. He had a true right limb shortening of 3.6 cm and limited range of motion. However, he had minimal functional disability. An X-ray of the pelvis and hip joints showed grade 4 osteoarthritis of the right hip joint with destruction of the right femoral head. There were three retained metallic nails (shrapnel) in the right hip joint of which two were intra-articular. Although he was offered a total hip arthroplasty, he opted for conservative management due to his minimal functional disability. Modified foot wear and simple analgesics were prescribed, and he had no worsening of symptoms at 6 months of follow up. Conclusion. Late presentation due to shrapnel-induced osteoarthritis with bone destruction and limb shortening is extremely rare. Initial assessment with radiographs is essential following blast injuries to exclude intra-articular or periarticular foreign bodies. Such foreign bodies should be removed to prevent the associated local and systemic complications.